Deteriorating Water Distribution Systems Affect Public Health. Issue 9 (5th September 2019) - Vacs Renwick, Deborah; Rotert, Kenneth
Abstract : Distribution system infrastructure issues can affect water reliability and quality and could contribute to waterborne disease outbreaks. It's important to know potential contamination mechanisms and consider rehab and replacement options.